Research and Development Center Administration System for Vocational Education in Thailand: Technique of Confirmatory Factor Analysis - Wanghom, Krittiya; Sisan, Boonchan; Tungkunanan, Pariyaporn (Journal of Technical Education and Training, 2020)
The objective of this research is to analyze the elements of the system of research and development center administration of vocational institutes in Thailand. The samples are 10 administrators of vocational institutes, 47 directors of academic institutes and 343 lecturers of the curricula, or 400 samples in total, selected with the stratified sampling technique. The tool used in this research is a questionnaire with the reliability value of 0.937. The primary assumption for the Exploratory Factor Analysis has the value of Kaiser Meyer-Olkin of 0.83, and the value from Bartlett's test of 1774.30, with the statistical significance level of 0.01. The outcomes from the CFA on the system of vocational education research and development center administration of vocational institutes in Thailand show that the concurrence with the empirical data is as follows: Ï‡2 = 1.22, p-value = 0.54, Ï‡2/df = 0.61, GFI = 1.00, RMSEA = 0.00, AGFI = 0.98. The weights of the elements fall in the range of 0.51- 0.86, as follows: The weight of the element of policy, vision, mission and strategy is 0.51, the weight of the element of research quality management is 0.57, the weight of the element of  budget management is 0.60, the weight of the element of publicity and public relations work is  0.66, the weight of the element of information system is 0.67, the weight of the element of monitoring and evaluation is 0.76, the weight of the element of intellectual property management is 0.80, the weight of the element of formation of organizational structure is 0.82, and the weight of the element of human resource management is 0.86.